2018
DOI: 10.1016/j.jcmg.2017.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine Therapy and Plaque Stabilization in Patients With Acute Coronary Syndrome

Abstract: Our findings suggest, for the first time, that low-dose colchicine therapy favorably modifies coronary plaque, independent of high-dose statin intensification therapy and substantial low-density lipoprotein reduction. The improvements in plaque morphology are likely driven by the anti-inflammatory properties of colchicine, as demonstrated by reductions in hsCRP, rather than changes in lipoproteins. Colchicine may be beneficial as an additional secondary prevention agent in patients post-ACS if validated in fut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
137
1
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 225 publications
(153 citation statements)
references
References 23 publications
4
137
1
11
Order By: Relevance
“…Colchicine is a widely available, tolerable, and inexpensive anti-inflammatory medication that prevents mitosis by inhibiting microtubule polymerization 1,8 but also interferes with several steps in the inflammatory process. It is used extensively in the management of gout, acute and recurrent pericarditis, and familial Mediterranean fever.…”
Section: Introductionmentioning
confidence: 99%
“…Colchicine is a widely available, tolerable, and inexpensive anti-inflammatory medication that prevents mitosis by inhibiting microtubule polymerization 1,8 but also interferes with several steps in the inflammatory process. It is used extensively in the management of gout, acute and recurrent pericarditis, and familial Mediterranean fever.…”
Section: Introductionmentioning
confidence: 99%
“…Its presumably adherent use of all FMF patients grants a satisfactory explanation for the low prevalence of IHD among FMF patients. Indeed , several studies found colchicine to lower levels of high sensitivity CRP in patients with stable coronary disease and to have a favourable effect on coronary plaque stability . Moreover, two randomised controlled trials reported reduced risk for cardiovascular events among high risk patients by using low dose colchicine …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies found colchicine to lower levels of high sensitivity CRP in patients with stable coronary disease 22 and to have a favourable effect on coronary plaque stability. 23 Moreover, two randomised controlled trials reported reduced risk for cardiovascular events among high risk patients by using low dose colchicine. 24,25 Considering the information accumulated so far, what brings our study to contradict the lack of association between FMF and IHD seen so far?…”
Section: Discussionmentioning
confidence: 99%
“…Colchicine is widely used, well tolerated, and effective for prevention and treatment of acute gout which is due to hyperuricemia. As uric acid crystals and cholesterol crystals are activated by the same pathway in the pathogenesis of atherosclerosis, colchicine can play a protective role in CVD patients by rapidly reducing high sensitivity C reactive protein (hs‐CRP), stabilizing the atherosclerosis plaque, and reducing cardiovascular events at low dose . Nevertheless, xanthine oxidase inhibitors, which are another agents used to lower SUA level, have not reduced mortality in patients with CVD .…”
Section: Discussionmentioning
confidence: 99%